LIFE AND ITS VALUE IN WORLD RELIGIONS - Manickam, Thomas (Journal of Dharma, 1996)
There are numerous perspectives about life and its values in relatlon to various sciences and disciplines. Scientifically speaking life is directly linked to protoplasm, the substance which is the highest known form of organic matter, The protoplasmis basically a system of life-structures and functions in which nucleic acids, carbohydrates, fats, hormones, vitamins and enzymes occur. This foundational living matter appears in a cellular organization. The cellular schema means that life is only present in an individualized form. The vital processes take place in and through the cellular structures of an individual, even that of a microscopic form. The basis of the .vltal processes is the metabolism of the cell, an interchange of materialswhich may, again be divided into a metabolism of nutrients and energy. The metabolism of the cell means that the IMng thing is a pulsating unit of life empoweredto bring about the:conttactionl of Its molecular elements which are the bases of all’immanent movements, the signs of the pulsation of life. So in scientific terms life is described as the vital -energy in a cellular organic material unit.